Trends and Issues of Ethnoscience Research from 2008 to 2023: A Bibliometric Analysis - Misbahul Jannah; M. Noris; Indriyani Indriyani (Jurnal Penelitian Pendidikan IPA, 2023)
This paper aims to analyze research trends on ethnoscience using bibliometric analysis from 2008-2023. The research sample consisted of 153 documents obtained from the Scopus database. The results of the study show that the distribution of publication frequency reaches its peak in 2021 with 32 articles identified. The distribution of research themes consists of 4 primary clusters and 35 secondary clusters. The ethnoscience research area is dominated by social science research (30.2%). The country with the best documents shows that Indonesia is ranked first as the most productive country in publishing on ethnoscience with 74 identified documents. The United States released second place with 28 documents, third Brazil with 10 documents, fourth Canada with 9 documents, and fifth France, Germany, Italy and the Russian Federation with 5 documents each. Institutions that contributed the most came from Indonesia, Universitas Negeri Semarang 22 papers 33.66%, University of Alberta 9 papers 13.77%, Universitas Negeri Surabaya 7 papers 10.71, Universitas Negeri Padang 7 papers 7.65%. The best author with the highest number of citations is Dahdouh. Meanwhile, if we look at the number of documents published by the author, Sudarmin has 10 documents with a contribution of 15.3%.